Analisis Pemahaman Konsep dan Kesulitan dalam Memahami Mata Kuliah Kalkulus 1 Mahasiswa Program Studi Matematika - Nur'aini Muhassanah (Scientific Timeline, 2021)
The purpose of this study is to find out: (1) understanding of the concept of calculus 1 for students of the mathematics study program, (2) what are the things that cause students difficulties in understanding the concept of calculus. In this research, the method used is qualitative with descriptive methods. Where the technique used to determine the source of data is the purposive sampling technique. The data taken in this study consisted of two, namely the results of the conceptual understanding test and the interview results. Triangulation methods will then validate the test results. The conclusions of this study's results are: first, the understanding of the concept of calculus 1 in mathematics study program students consists of 13.64% in the high category, 40.91% in the medium category, and 45.45% in the low category. Second, three things cause students difficulties in understanding the concept of calculus 1; they are the methods or learning models used by lecturers, student's lack of questions' exercise by the students, student's lack of repeating the materials given by the lecturer. Besides all of that, basic mathematical concepts during high school are also insufficient to go through the next level of calculus learning.